2016
DOI: 10.1177/1460458215590250
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of utilizing a commercial eye tracker to assess electronic health record use during patient simulation

Abstract: Numerous reports describe unintended consequences of electronic health record implementation. Having previously described physicians' failures to recognize patient safety issues within our electronic health record simulation environment, we now report on our use of eye and screen-tracking technology to understand factors associated with poor error recognition during an intensive care unit-based electronic health record simulation. We linked performance on the simulation to standard eye and screen-tracking read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Alternatively, it represents a coping strategy for an EHR system that does not automatically provide an effective visual display of data needed for daily rounds. Our prior work showed that in order to recognize patient safety issues in simulated MICU patient cases, clinicians had to visit over 30 different EHR screens (15, 35). Thus, the value of the prerounding artifact may be that it gives clinicians a standardized data collection script and creates a single visual display of all rounding data that are otherwise geographically fragmented within the EHR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it represents a coping strategy for an EHR system that does not automatically provide an effective visual display of data needed for daily rounds. Our prior work showed that in order to recognize patient safety issues in simulated MICU patient cases, clinicians had to visit over 30 different EHR screens (15, 35). Thus, the value of the prerounding artifact may be that it gives clinicians a standardized data collection script and creates a single visual display of all rounding data that are otherwise geographically fragmented within the EHR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inexperience has been associated with more gaze fixations, orderly search patterns, and visual neglect of important information, all of which have been observed to correlate with cognitive workload during EHR review (Moacdieh & Sarter, 2015). We have shown that gaze fixation data can predict a user's ability to recognize patient safety issues during simulated ICU rounds (Gold, Stephenson, Gorsuch, Parthasarathy, & Mohan, 2016). These associations provide the basis for using quantitative eye-tracking metrics as surrogates for performance during EHR review tasks.…”
Section: Introductionmentioning
confidence: 80%
“…This role mirrors our real rounds in which the order writer is often not directly involved in the care of the patient being discussed. Workstations were equipped with Tobii studio eyetracking as previously described to allow observation of participants' pre-rounding processes [14]. Once pre-rounding was complete, the intern, nurse, pharmacist and resident gathered to round.…”
Section: Methodsmentioning
confidence: 99%